Poly(Pentafluorophenyl Methacrylate)‐Based Nano‐Objects Developed by Photo‐PISA as Scaffolds for Post‐Polymerization Functionalization. Issue 2 (30th July 2018) - Couturaud, Benoit; Georgiou, Panagiotis G.; Varlas, Spyridon; Jones, Joseph R.; Arno, Maria C.; Foster, Jeffrey C.; O'Reilly, Rachel K.
Abstract: The preparation of a functional fluorine‐containing block copolymer using reversible addition–fragmentation chain‐transfer dispersion polymerization in DMSO as a "platform/scaffold" is explored. The nanostructures, comprised of poly(ethyleneglycol)‐ b ‐poly(pentafluorophenyl methacrylate) or PEG‐ b ‐P(PFMA), are formulated via photo‐initiated polymerization‐induced self‐assembly (PISA) followed by post‐polymerization modification using different primary amines. A combination of light scattering and microscopy techniques are used to characterize the resulting morphologies. It is found that upon varying the degree of polymerization of the core‐forming block of PFMA, only uniform spheres (with textured surfaces) are obtained. These nanostructures are subsequently modified by cross‐linking using a non‐responsive and a redox‐responsive diamine, thus imparting stability to the particles in water. In response to intracellular glutathione (GSH) concentration, destabilization of the micelles occurs as evidenced by dynamic light scattering. The well‐defined size, inherent reactivity of the nanoparticles toward nucleophiles, and GSH‐responsiveness of the nanospheres make them ideal scaffolds for drug delivery to intracellular compartments with reductive environments. Abstract : Poly(ethylene glycol)‐ b ‐poly(pentafluorophenyl methacrylate) diblock copolymer nano‐objects are prepared via photo‐initiated polymerization‐induced self‐assembly (PISA) in DMSO followed by cross‐linking reactions using either ethylenediamine (non‐responsive) or cystamine (glutathione (GSH) responsive) for stabilization into aqueous media.